Update on the Major Clonal Types of Methicillin-Resistant Staphylococcus aureus in the Czech Republic - Melter, O. (American Society for Microbiology, 2003)
The purpose of our study was the molecular characterization of methicillin-resistant Staphylococcus aureus (MRSA) strains isolated in 21 hospitals in the Czech Republic in the period 2000-2002 and comparison with previous results from 1996-1997. Strains were analyzed by pulsed-field gel electrophoresis (PFGE) of SmaI digests and ribotyping of HindIII digests hybridized with a 16S-23S DNA probe. The prevalence of the most clinically important macrolide (ermA, ermB, ermC, and msrA) and aminoglycoside (aph3′, ant4′, and aac6′-aph2") resistance genes was evaluated as well. Selected isolates representative of each clonal type were analyzed by multilocus sequence typing and by a multiplex PCR method capable of identifying the structural type of the staphylococcal cassette chromosome mec (SCCmec) carried by the bacteria. Our results document the displacement of the Brazilian clone (ST239, SCCmec type IIIA, PFGE type B, ribotype H1) by a new clone that we named “Czech clone” (ST239, SCCmec type IIIA, PFGE type F, ribotype H6) and the maintenance of the Iberian clone (ST247, SCCmec type IA, PFGE type A, ribotype H2) exclusively in one hospital in the Czech Republic. In addition, we found a correlation between the distribution of aminoglycoside resistance genes and MRSA clonal types.